2022
DOI: 10.3389/fimmu.2022.947885
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors are a key bottleneck in tumor metabolic reprogramming: The prime suspect in cancer therapeutic resistance

Abstract: ATP and other nucleoside phosphates have specific receptors named purinergic receptors. Purinergic receptors and ectonucleotidases regulate various signaling pathways that play a role in physiological and pathological processes. Extracellular ATP in the tumor microenvironment (TME) has a higher level than in normal tissues and plays a role in cancer cell growth, survival, angiogenesis, metastasis, and drug resistance. In this review, we investigated the role of purinergic receptors in the development of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 214 publications
0
5
0
Order By: Relevance
“…In this model, eATP induces and regulates drug resistance spatially and temporally through multiple pathways and processes. First, eATP induces drug resistance extracellularly by binding to and activating purinergic receptors (PRs) located on the plasma membrane of cancer cells ( 29 31 , 44 , 45 ). The activated PRs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, eATP induces and regulates drug resistance spatially and temporally through multiple pathways and processes. First, eATP induces drug resistance extracellularly by binding to and activating purinergic receptors (PRs) located on the plasma membrane of cancer cells ( 29 31 , 44 , 45 ). The activated PRs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all sunshine and roses, the therapeutic landscape of HCC is punctuated by instances of resistance to immune checkpoint therapies. This phenomenon of immunotherapy resistance is both intricate and multifaceted, often serving as a significant bottleneck to realizing the full therapeutic potential of these novel interventions ( Zhang et al, 2021 ; Aria et al, 2022 ). It is within this challenging context that our study attempts to shed light on the molecular actors that might play pivotal roles in determining treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal changes in the Purinergic pathway may lead to the development of various diseases, including many cancers [9]. Recent studies have shown that tumor cells can use the Purinergic pathway to promote their proliferation, invasion, angiogenesis, and immune escape by increasing the production and release of purine nucleotide derivatives and altering the expression and sensitivity of Purinergic receptors [10]. At the same time, immune cells in the tumor microenvironment can also interact with tumor cells through the Purinergic pathway, thereby affecting tumor cell growth and metastasis [11].…”
Section: Introductionmentioning
confidence: 99%